Periconium sp. (endophytic fungi) extract mediated sol-gel synthesis of ZnO nanoparticles for antimicrobial and antioxidant applications. (January 2020) - Ganesan, V.; Hariram, M.; Vivekanandhan, S.; Muthuramkumar, S.
Abstract: The Periconium sp. extract mediated sol-gel process was effectively utilized for the synthesis of ZnO nanoparticles. The aqueous fungal extract acted as chelating agent for the Zn 2+ ions and lead to the formation of gel. The dried gel was characterized by X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscope (SEM), Thermogravimetric/differential thermal analysis (TG/DTA) respectively to identify their phase, structural coordination, morphological feature and thermal degradation profile. The XRD analysis reveals that the biosynthesized ZnO nanoparticles are exist in hexagonal wurtzite structure with the average crystallite size of 40 nm. Transmission electron microscopic (TEM) images of the synthesized ZnO nanoparticles did show the quasi spherical shape with 16–78 nm in size. The Dynamic Light Scattering (DLS) analysis showed their zeta potential and hydrodynamic particle size respectively as −88.6 mV and 338 nm. The UV–Visible spectroscopic analysis depicts their band gap energy as 3.15 eV. The synthesized ZnO nanoparticles exhibited excellent antimicrobial activity against Staphylococcus aureus (Gram positive), Escherichia coli (Gram negative) and Candida albicans ( fungi) with an average inhibition zone of 16, 14 and 24 mm, minimum inhibitory concentration (MIC) value of 50, 50, 40 μg/ml, the minimum bactericidal/fungicidal concentration (MBC/MFC) of 50 μg/ml and the half maximal inhibitory concentration (IC50 ) of 22, 38 and 21 μg/ml respectively. Further, the ZnO nanoparticles also exhibited good antioxidant property with the 85.52% free radical quenching for 100 μg/ml concentration.